Carcinosarcoma of the Thyroid Gland - Mehmet Fatih Ekici; Cengiz Kocak; Zülfü Bayhan; Sezgin Zeren; Faik Yaylak; Mehmet Hüseyin Metineren; Fatma Emel Kocak (Case Reports in Surgery)
Introduction. Surgeon has significant role in the management of such rare and controversial clinical entities related to thyroid gland. In this case report we have presented an elderly patient with rapid enlargement in thyroid that was related to carcinosarcoma. Case Presentation. A 60-year-old lady was presented with rapid enlargement of the thyroid gland. A fine needle aspiration of the nodule in right lobe was performed several weeks before presentation to our clinic. End diagnosis was a papillary carcinoma of the thyroid with spindle cell component. Thus the nodule was recognized to be a carcinosarcoma. Conclusion. Thyroid surgery merits a multidisciplinary approach. Indeed the surgeon should make a conclusive decision in some controversial and rare clinical entities such as carcinosarcoma.